The Relationship between Diet and Physical Activity: A Case Study of Obesity in Adolescents in the Modern Ngawi Vocational School Environment - Setyadi, Fantas (LPPM Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
As time goes by, students' diets are increasing and physical activity is decreasing. This is due to the lack of movement that occurs in students in the modern era. The purpose of this study is to determine the diet and physical activity in the case study of Obesity in adolescents. This type of research is a correlational research with a cross sectional study approach. The sample used was 30 students on the basis of sampling using the total sampling technique. Dietary data collection techniques using research questionnaires, physical activity data collection using GPAQ questionnaires and obesity data collection were carried out weight and height measurements. Data analysis uses product moment correlation. The results show that: 1) There was a relationship between diet and the incidence of obesity in adolescents with a value of Fcount > Ftable (0.778>0.374), 2) There was a relationship between physical activity and obesity in adolescents with a value of Fcount > Ftable (0.433>0.374), 3) There was a relationship between diet and physical activity and the incidence of obesity in adolescents with a value of Fcount > Ftable (20.510>3,592). Based on the results of the study, it can be concluded that most of the respondents have a bad diet, in addition to that most of the respondents who have low physical activity < 600 MET and most of the respondents are obese. So that the implication of this study is to increase health promotion regarding risk factors regarding obesity and non-communicable diseases and further improve healthy programs by holding joint gymnastics for adolescents at SMK Modern Ngawi every week